2022
DOI: 10.1126/sciadv.abm9027
|View full text |Cite
|
Sign up to set email alerts
|

The role of ipRGCs in ocular growth and myopia development

Abstract: The increasing global prevalence of myopia calls for elaboration of the pathogenesis of this disease. Here, we show that selective ablation and activation of intrinsically photosensitive retinal ganglion cells (ipRGCs) in developing mice induced myopic and hyperopic refractive shifts by modulating the corneal radius of curvature (CRC) and axial length (AL) in an opposite way. Melanopsin- and rod/cone-driven signals of ipRGCs were found to influence refractive development by affecting the AL and CRC, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…However, it has been proposed that these effects are due to activation of melanopsin (OPN4), which would not be activated by the red light used here. 34 If the red light-induced hyperopia is due to stimulation of longer wavelength cones and lack of stimulation of shorter wavelength cones, then we should expect the effect to be robust with changes in lighting intensity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been proposed that these effects are due to activation of melanopsin (OPN4), which would not be activated by the red light used here. 34 If the red light-induced hyperopia is due to stimulation of longer wavelength cones and lack of stimulation of shorter wavelength cones, then we should expect the effect to be robust with changes in lighting intensity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that lncRNA Gm35369 might be related to myopia, and this lncRNA is mainly located in ganglion cells and horizontal cells [ 14 ]. Studies have reported that RGC alterations are associated with the occurrence and development of myopia, including changes in the number of RGCs, abnormal axonal projections and changes in protein expression in RGCs [ 19 22 , 38 ]. However, whether lncRNAs in RGCs are involved in the pathogenesis of myopia and the role of lncRNAs as ceRNAs in myopia are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have shown that light can also regulate nociception [25,26]. And finally, the light environment may exert an important role during development, including neonatal aversive behaviours [27,28], retinal vasculature development [29], ocular growth associated with myopia [30,31] and synapse formation in the brain [32]. Together, these data illustrate the wide-ranging influence of light on mammalian physiology and behaviour (Figure 1).…”
mentioning
confidence: 84%
“…Indeed, it is now apparent that, in mice, spectral signals originating from cones influence neural activity within the master circadian clock (the suprachiasmatic nucleus) and can modulate the timing and robustness of behavioural and physiological rhythms [6,89]. Finally, there are emerging data of a protective role of 'violet' (360-400nm) light against the development of myopia in mice and other species via as yet incompletely resolved mechanisms [30,31,[90][91][92][93][94].…”
Section: Species Specific Consideration Of 'Colour'mentioning
confidence: 99%